2020
DOI: 10.1101/2020.06.08.20124974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal Characterization of the Tumoral Microbiome during Radiotherapy in HPV-associated Oropharynx Cancer

Abstract: Purpose: To describe the baseline and serial tumor microbiome in HPV-associated oropharynx cancer (OPC) over the course of radiotherapy (RT). Methods: Patients with newly diagnosed HPV-associated OPC treated with definitive radiotherapy +/- concurrent chemotherapy were enrolled in this prospective study. Using 16S rRNA gene sequencing, dynamic changes in tumor microbiome during RT were investigated. Surface tumor samples were obtained before RT and at week 1, 3 and 5 of RT. Radiological primary tumor response … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The dynamic variation of the GM over the course of NAC in bladder cancer has not been studied, however, studies within colorectal[29], head and neck[30] and cervical cancer [31] [32]have all demonstrated significant fluctuations in composition. It is therefore not surprising, that the longitudinal microbiota fluctuations in our study are mostly driven by an increase in Bacteroides abundance during the course of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic variation of the GM over the course of NAC in bladder cancer has not been studied, however, studies within colorectal[29], head and neck[30] and cervical cancer [31] [32]have all demonstrated significant fluctuations in composition. It is therefore not surprising, that the longitudinal microbiota fluctuations in our study are mostly driven by an increase in Bacteroides abundance during the course of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Schuurhuis et al followed a cohort of 26 and 27 oral or oropharyngeal cancer patients treated with radiotherapy and radiochemotherapy respectively and found that, when compared to patients treated with surgery alone, patients treated with radiotherapy had increased abundance of enteric rods, staphylococci and Candida one year after treatment [77]. Finally, another small study reported a shift in the composition of the bacterial community, with Actinomyces and Leptotrichia declining over the course of radiation, while Veillonella and Atopobium increased [36].…”
Section: Impact Of Radiotherapy On the Microbiotamentioning
confidence: 99%
“…Noteworthy, the majority of studies elaborating on the composition of the tonsillar microbiome have analyzed tissues from pediatric patients [14][15][16][17][18][19][20][21]. Tonsil cancer occurs only in adults and the few available datasets on the adult microbiome in tonsil cancer have not considered the inclusion of age-matched control cohorts [22,23]. Here, we have analyzed the tonsillar crypt microbiome from two different patient cohorts.…”
Section: Introductionmentioning
confidence: 99%